Age and Peer Victimization among School Adolescents in Kathmandu, Nepal - Neupane, Dasrath (Journal of Advanced Academic Research, 2015)
Bullying or peer victimization is an intentional harassment that occurs when there is a power imbalance between individuals or groups. It is assumed that peer victimization varies with age. The present study was conducted to explore the correlation of victimization to age among school adolescents in Kathmandu, Nepal. The study uses a quantitative approach. It is correlational in design employing a pen-and-paper self-report survey. There were 524 students from 4 public and 4 private schools of grade 8 and 10 students. The result of the study diverges from the findings reported in previous literature. Findings in terms of age-related associations do not follow patterns generally predicted by theory or previous research, because, as this study shows there are no significant relationships between age and any form of bullying or victimization. Journal of Advanced Academic Research Vol.1(1) 2014: 18-23